Empirical Analysis of the Hugh Gray 'Nessie' Photograph - Watson, Roland (Journal of Scientific Exploration, 2022)
The first photograph said to be of the Loch Ness Monster was taken on 12th November 1933 around noon by a local man by the name of Hugh Gray. I say "Loch Ness Monster" because I believe the photograph to be genuine and part of the evidence portfolio. The picture that generally circulates is shown below. The Scottish Daily Record took his picture and Mr. Gray gave the following account to them having been interviewed by Hugh Mackenzie (the future Provost of Inverness), Peter Munro representing Hugh Gray's employers at the British Aluminium Company and a Daily Record staff member: Four Sundays ago, after church I went for my usual walk near where the river enters the Loch. The Loch was like a mill pond and the sun shining brightly. An object of considerable dimensions rose out of the water not very far from where I was. I immediately got my camera ready and snapped the object which was two or three feet above the surface of the water. I did not see any head, for what I took to be the front parts were under the water, but there was considerable movement from what seemed to be the tail, the part furthest from me. The object only appeared for a few minutes then sank out of sight. A contemporary picture of Hugh Gray was printed later which I don't think flatters him much but is shown below to show you the man behind the monster. The tenor of the account suggests some throwing up of spray and water as the presumed tail beat about the waters and hence caused some blurriness around that region of the picture. Mackenzie described Gray as a man highly respected by his fellow workmen, employers and locals. Likewise, the Daily Record had the negative examined by four experts who deemed it as untampered. It caused a stir, was panned by zoologists and faded along with general Nessie-lore as the World entered war six years later. Twenty-two years on, Nessie author, Constance Whyte, visited Hugh Gray in May 1955 who was sticking to his story and still had vivid memories of that day plus he also recounted five other times he claimed to have seen the monster over those decades. Renowned monster hunter, Tim Dinsdale, also recounts how he visited Gray in April 1960 and described him as "a most courteous individual" as he took him to the spot of the sighting[4]. He spoke with "complete conviction" about that day as well as maintaining an accuracy of his account. He also added some detail of his other sightings which partly consisted of rapidly moving bow waves with no visible cause. What remains of the photograph today is uncertain.